1999
DOI: 10.1136/pgmj.75.884.339
|View full text |Cite
|
Sign up to set email alerts
|

The effect of passive smoking on pulmonary function during childhood

Abstract: SummaryPassive smoking, especially of maternal origin, is known to influence adversely the development of children's pulmonary function. In this study, the eVect of parental smoking on the pulmonary function of 360 primary school children aged 9-13 (mean 10.8±0.7) years was investigated. Information on parental smoking history was collected using a questionnaire, and spirometric measurements were performed on the children.All spirometric indices were lower in children who had been passively exposed to parental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 15 publications
1
18
0
3
Order By: Relevance
“…Schwartz et al (2000) found that exposure to cigarette smoke was associated with a decrease in peak expiratory flow rate (PEFR). Passive smoking was found to be associated with reduced PEFR, forced expiratory volume in 1 s (FEV1) and forced expiratory flow rate between 25% and 75% of forced vital capacity (FVC) (Bek et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Schwartz et al (2000) found that exposure to cigarette smoke was associated with a decrease in peak expiratory flow rate (PEFR). Passive smoking was found to be associated with reduced PEFR, forced expiratory volume in 1 s (FEV1) and forced expiratory flow rate between 25% and 75% of forced vital capacity (FVC) (Bek et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Parents who smoke endanger themselves, put children and spouses at risk for adverse health outcomes, and increase the chance that their children will become smokers. 4,5 Parents who smoke 1 pack per day spend approximately $1500/y on cigarettes.…”
mentioning
confidence: 99%
“…These include otitis media, bronchitis, bronchiolitis, wheeze, cough, asthma, and pneumonia. [3][4][5][6][7][8] Long-term adverse outcomes include cognitive impairment, reduced lung function and development, and deficits in reading, math, and visiospacial reasoning. 7,[9][10][11][12][13] Often, the conditions caused by TSE result in the need for medical care.…”
mentioning
confidence: 99%